Configurable kinetics of polarization switching via ion migration in ferroionic CuInP2S6 - Lei Liang; Er Pan; Guiming Cao; Jiangang Chen; Ruixue Wang; Biao Dong; Qing Liu; Xiong Chen; Xiao Luo; Yongfa Kong; Wenwu Li; Fucai Liu (Nature Communications)
Abstract Ferroelectric materials are promising for developing non-volatile memory, neuromorphic computing, and photovoltaic technologies. Taking advantage of variable switching kinetics provides an important strategy for designing multifunctional ferroelectric devices. However, the conventional ferroelectrics due to the unmovable atomic species generally own a single switching kinetics, thus versatile and configurable switching kinetics still remain challenging. In this work, we systematically investigate the switching kinetics of the van der Waals ferroionic CuInP2S6 through polarization-determined ferroelectric photovoltaic behaviors. Based on the time- and field-dependent polarization switching and numerical simulation, we discover three switching modes, including intralayer switching, interlayer switching and intralayer-interlayer coupling switching in CuInP2S6. Through designing the poling voltage amplitude and width, we achieve the configurable kinetic control of polarization switching in CuInP2S6, enabling tunable binary, gradual and accumulative switching with defined poling voltages in a single device. The work demonstrated here is instructive for the development of nanoscale multifunctional ferroelectric devices.